2022
DOI: 10.1155/2022/9997531
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Detection and Diagnostic Value of Cytokines in Serum of Children with Acute Viral Encephalitis

Abstract: Acute viral encephalitis is one of the serious infectious diseases. In order to analyze the diagnostic efficacy of serum procalcitonin (PCT), C-reactive protein (CRP), and S100B protein in acute viral encephalitis, a total of 100 children with acute viral encephalitis from July 2019 to December 2021 are selected and included in the viral encephalitis group. The results show that S100B protein model has high specificity and sensitivity and is simple to operate. It provides new ideas and directions for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%